Smart and sassy the strengths of inner city Black girls - Stevens, Joyce West, 1936- (New York ; Oxford : Oxford University Press, 2002)
Empirically based, the daily experiences of adolescent black females is explicated within an explanatory model of social context and developmental theory. The author argues that adolescence must be seen from strength and health perspectives.
Description based on print version record.
Includes bibliographical references and index.
Keywords: African American teenage girls -- Attitudes; African American teenage girls -- Psychology; African American teenage girls -- Social conditions; Adolescence -- United States